The Clinical Course of Multiple Myeloma in the Era of Novel Agents: A Retrospective, Single-Center, Real-World Study - Agoston Gyula Szabo; Katrine Fladeland Iversen; Sören Möller; Torben Plesner (Clinical Hematology International, 2019)
In this retrospective study we reviewed the clinical course of every patient with multiple myeloma treated from 2006 to 2016 at Vejle Hospital: 303 patients with a median age of 69 years at diagnosis received a median of four (range 1–18) lines of therapy; 149 in a 2006–2010 cohort and 154 in a 2011–2016 cohort. After initiation of treatment, the median decrease in the number of patients per each subsequent line of therapy was 22%. Lenalidomide-dexamethasone (n = 156), bortezomib-dexamethasone (n = 107), and bortezomib-lenalidomide-dexamethasone (n = 84) were the most commonly used regimens. The partial response or better rate was 78%, 58%, 55%, and 44% in lines of therapy one to four, respectively. The median (95% confidence interval [CI]) progression-free survival was 18 (15–22), 10 (8–13), 8 (7–10), and 6 (4–8) months in lines of therapy one to four, respectively. The median (95% CI) overall survival (OS) was 4.1 (3.7–4.8) years. Compared with the 2006–2010 cohort, patients in the 2011–2016 cohort had longer OS; 5.3 (4.7 to not reached) versus 3.4 (2.7–4.0) years, p < 0.0001. This was especially true in patients not treated with high-dose therapy and autologous stem cell transplantation; 4.7 (3.2–5.9) versus 2.6 (2.0–3.3) years, p = 0.0052. Patients in the 2011–2016 cohort were on treatment during a greater part of their life and had higher exposure to high-dose melphalan with autologous stem cell transplantation, lenalidomide, pomalidomide, daratumumab, and carfilzomib.